Pengaruh Jenis Ransum Komersial Pada Dua Strain Ayam Broiler Terhadap Produksi Karkas - Adu, Lody Frydolin; Suryatni, Ni Putu F.; Theedens, Jonas F.; Mulyantini, N.G.A; Enawati, Luh Sri (Animal Agricultura, 2025)
This study aims to determine the effect of different types of commercial rations and different strains on carcass production. The method used is the 2×3 factorial pattern CRD method. The first factor is 2 strains of chicken (Strain A and Strain B), the second factor is 3 types of commercial rations (P1 ration, P2 ration and P3 ration) so that there are 6 treatment combinations. Each treatment was repeated 4 times, each replicate consisted of 4 chickens. This study used 96 broiler chickens. The variables measured were final weight, percentage of carcass, non-carcass and abdominal fat. The results of statistical analysis showed that there was no interaction (P>0.05) between commercial ration type factors and strain types on all variables. Based on the results of this study, it was concluded that there was no interaction between the provision of commercial ration types in two broiler chicken strains to carcass production, which means that the three ration types could be given to two strains without affecting broiler chicken carcass production.